Thinking about Outputs: Towards a Bibliographic Database for the Humanities and Social Sciences - Žic Fuchs, Milena (2010)
Keynote adresses issues on how to enhance the visibility of research outputs in the Humanities and Social Sciences, how to set up evaluation systems for SSH. The unsuccessful evaluation on the basis of WoS, SCOPUS etc. is discussed. A new report on bibliographic databases shows full possibilities of mirroring the outputs of European research in the Humanities and Social Sciences, that is, their specific nature in regard to national languages, as well as specific nature in the specificity of outputs.
Projekt MZOS
ENG